Geochemical simulation to assess the rock–water interaction in crystalline aquifers in São Paulo State, Southeastern Brazil - Teramoto, Elias Hideo [UNESP]; Stradioto, Marcia Regina [UNESP]; Chang, Hung Kiang [UNESP] (Springer Nature, 2023)
The mechanisms underlying rock–water interactions play a crucial role in understanding groundwater quality. In this study, we examined hydrochemical data from 96 samples obtained from the crystalline aquifer system in the Southeast region of São Paulo State, Brazil, to characterize the hydrochemistry of these aquifers. Through the analysis of these data, we conducted several geochemical simulations to reproduce the hydrochemistry of the evaluated samples. Our analysis revealed two distinct evolutionary trends in hydrochemistry. The calcium–magnesium bicarbonate types can be attributed to the dissolution of amphiboles, while the sodium bicarbonate type can be reproduced by the dissolution of plagioclases. Contrary to the initial assumptions, the hydrochemistry of the evaluated samples does not mimic the mineralogy of the granitic/gneiss rocks. Instead, the cations dissolved in groundwater mainly originate from unstable and reactive minerals, primarily represented by amphiboles and plagioclases. Furthermore, considering that HCO3− is the primary species generated through silicate hydrolysis in an open system with respect to CO2, we have developed a model that utilizes the concentration of this ion as a parameter to estimate the mass of rock involved in the rock–water interaction process. This model allows us to assess the extent of rock–water interaction based on HCO3− concentration. However, this approach is only valid in cases where additional sources of HCO3− are absent, and elevated PCO2 levels prevent an increase in pH and carbonate precipitation. Overall, our findings make significant contributions to the comprehension of rock–water interaction processes and the assessment of groundwater quality in crystalline aquifers. However, they challenge the prevalent belief that the hydrochemistry of crystalline aquifers closely mirrors that of the fissured rocks through which groundwater flows.
Keywords: Crystalline basement; Mineral water; Rock–water interaction; Silicate dissolution